Isolation of Rhizobium Spp. Bacteria which as Used Microbial Fertilizer from Wild Leguminosarum Plants - Hatice Öğütcü; Ömer Faruk Algur (Turkish Journal of Agriculture: Food Science and Technology, 2014)
In our study used wild leguminous plants (Medicago sativa, M. lupulina and M. varia ) Erzurum belongs to the high altitude (2000 - 2500m ) regions ( Palandöken mountain, Alibaba mountain, Turnagöl mountain, Hasanbaba mountain, Eğerli mountain, Yıldırım mountain, Çubuklu mountain, Deveboynu locality, Kayakyolu locality, Telsizler and Dumlu hill ) were collected during the months of June and July. Nodules were obtained from this plant were sterilized, YMA (Yeast Mannitol Agar) plates were streaked and petri dishes 28+1ºC were incubated for 3-5 days. Colonies appear after incubation typically constitute (white, clear or slightly opaque, mucosity, round, raised) 39 isolates were selected and transferred to tubes and refrigerated YMA were stored at +4ºC. In the next stage, cytological and biochemical analyzes of these isolates were studied to determine. For this purpose isolates; YMA containing bromothymol blue and congo red reproduction, gram stain reaction, movement and subjected to catalase and oxidase tests were evaluated. The cytological and biochemical analysis of results showed that 28 of 39 strains belonged to Rhizobium spp.